Pendekatan Metode ABC Pada Toko X untuk Pengendalian Persediaan Barang - Firman Ardiansyah Ekoanindiyo; Ermayana Megawati; Jihan Pradesi; Dewi Zainul Khabibah (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
Retail industry competition is so tight, one of which is cost efficiency, which can be done by controlling inventory. Store X is one of the modern retail stores in Indonesia. Store X sells various types of fast-moving consumer goods (FMCG). The company implements a make to stock system to meet consumer demand. The amount of inventory in the warehouse is not in accordance with consumer demand so that there is a buildup of goods in the warehouse which results in high inventory costs. In addition, some of the goods sold have low stock, even though there is a lot of consumer demand. Conditions like this will result in losses for the company. Category A 30% total goods Rp. 38.235.557,-. Classification B 20% total goods worth Rp. 7.748.157,-. Category C 50%. value of Rp. 4.552.842,- Economical order at shop X, for stock of item A, namely mineral water A PET 600 ml, the order is made when stock is 7 pcs, safety stock is 46 pcs. Mineral water A PET 1500 ML ordering supplies 7 pcs, safety supplies 52 pcs. Bear brand milk 12 ml with order when stock is 11 pcs, safety stock 39 pcs.